The Wavelength-Shifting Optical Module in Application to the IceCube Neutrino Observatory - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Proceedings of Science, 2024)
The Wavelength-shifting Optical Module (WOM) is a novel photosensor concept developed as part of the upcoming Upgrade for the IceCube Neutrino Observatory. It uses the technique of wavelength shifting and total internal reflection to increase the photon light yield in the UV-regime of the Cherenkov spectrum. The decoupling of the effective area from the size of light sensors enhances the signal-to-noise-ratio. Twelve WOM modules will be deployed in the IceCube Upgrade to increase the photon detection efficiency and thus enhance future low-energy analyses. The general concept can also be applied at the future IceCube-Gen2 detector, where passive light collecting extensions to the optical sensor modules locally increase the light collection efficiency. This technique would benefit the detection of supernova neutrinos or other particles with low light emissions. We report on new results in characterizing and optimizing the WOM concept, the production status of the modules to be deployed in 2025/26 as well as possible applications of the concept for IceCube-Gen2.
CRIS-Team Scopus Importer:2025-02-04